2006
DOI: 10.1086/504417
|View full text |Cite
|
Sign up to set email alerts
|

The Effective Temperatures and Physical Properties of Magellanic Cloud Red Supergiants: The Effects of Metallicity

Abstract: International audienceWe present moderate-resolution spectrophotometry of 36 red supergiants (RSGs) in the LMC and 37 RSGs in the SMC. Using the MARCS atmosphere models to fit this spectrophotometry, we determine the stars' physical properties and compare the results to evolutionary models. The (V-R)0 broadband colors agree with those from fitting the optical spectrophotometry, but (V-K)0 results show metallicity-dependent systematic differences in the physical properties. We conclude that this is likely due t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

40
383
3
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 205 publications
(428 citation statements)
references
References 33 publications
40
383
3
2
Order By: Relevance
“…This varying selection efficiency for different spectral types is of paramount importance when devising surveys for galaxies other than our own. It has been shown that the average spectral type of the RSG population depends on metallicity (Humphreys 1979a;Elias et al 1985;Levesque et al 2006;Levesque & Massey 2012) and so as Z decreases, more RSGs will have earlier types, moving slowly into the region where selection completeness is worse. Although these effects are very difficult to evaluate a priori just based on photometric data, one clear solution is to open the accepted Q range.…”
Section: Completeness Of the Samplementioning
confidence: 99%
See 1 more Smart Citation
“…This varying selection efficiency for different spectral types is of paramount importance when devising surveys for galaxies other than our own. It has been shown that the average spectral type of the RSG population depends on metallicity (Humphreys 1979a;Elias et al 1985;Levesque et al 2006;Levesque & Massey 2012) and so as Z decreases, more RSGs will have earlier types, moving slowly into the region where selection completeness is worse. Although these effects are very difficult to evaluate a priori just based on photometric data, one clear solution is to open the accepted Q range.…”
Section: Completeness Of the Samplementioning
confidence: 99%
“…In addition, Davies et al (2010) showed that RSGs can be used as abundance probes, opening up a new method to study the metallicity in other galaxies. Finally, the physical characteristics of RSGs vary for different metallicities (Humphreys 1979a;Elias et al 1985;Levesque et al 2006;Levesque & Massey 2012), but the number of known RSGs beyond the Galaxy and the Magellanic Clouds (MCs) is very low (Levesque 2013), and there is not a complete sample of RSGs in any Galaxy, not even the relatively nearby MCs.…”
Section: Introductionmentioning
confidence: 99%
“…We used the B − V and V − K vs. T eff calibrations by Alonso et al (1999) for the RGB stars of NGC 6192, whereas we used V − K vs. T eff calibrations by Levesque et al (2006) for the post-RGB stars of NGC 6404 and NGC 6583. Surface gravities were derived using the expression…”
Section: Stellar Parametersmentioning
confidence: 99%
“…The apparent magnitudes are transformed into absolute magnitudes using the distances and reddening values in Table 1. The bolometric corrections to be applied to M V in order to obtain M bol are taken from Alonso et al (1999) for giant stars and from Levesque et al (2006) for post-RGB stars. The masses were derived from the isochrones of Girardi et al (2000) using the estimated ages of each cluster (see Table 1).…”
Section: Stellar Parametersmentioning
confidence: 99%
“…The LGGS photometry is consistent with the color and brightness of a RSG. Indeed, following Levesque et al (2006), we found that, as an RSG, J0045+41 would have an effective temperature of ∼3500 K and bolometric magnitude of -6.67, consistent with a 12-15 M ⊙ RSG. However, a complete SED fit to photometry from the Panchromatic Hubble Andromeda Treasury (PHAT, Dalcanton et al2012) using the Bayesian Extinction and Stellar Tool (BEAST, Gordon et al 2016) yields an unphysical result of 300 M ⊙ , 10 5 K star, extincted by A V ∼4 magnitudes.…”
Section: J0045+41mentioning
confidence: 63%